The Influence of Facilities and Capabilities through Work Commitment on Employee Performance in the Pasar District of Jambi City - Yunita Wijayanti Jumady; Pantun Bukit; Osrita Hapsara (Dinasti Publisher, 2025)
This study aims to identify and understand the overview of work facilities, work capabilities, work commitment, and employee performance in the Pasar District of Jambi City. Additionally, it seeks to examine and analyze the influence of work facilities and work capabilities on employee performance, both directly and indirectly through employee commitment in the Pasar District of Jambi City. The research was conducted in the Pasar District of Jambi City, which consists of one district office and four sub-district offices. The total population comprises 68 employees as of 2023. This study employs a saturated sampling technique, where all members of the population are used as the sample. A quantitative approach was applied, utilizing a survey method and data analysis through Partial Least Squares (PLS). The results indicate that work facilities and work capabilities positively and significantly affect employee performance both directly and indirectly through work commitment. Likewise, work commitment directly has a positive and significant impact on performance. This means that if the available work facilities support employee comfort and effectiveness in carrying out their tasks, coupled with strong capabilities to perform their duties smoothly and achieve established goals, it not only directly enhances employee performance but also strengthens their commitment to the organization.